Idolatría y verdadera religión en la Historia Eclesiástica Indiana de Gerónimo de Mendieta (1571-1596) - Fracas, Simone (Studi e materiali di storia delle religioni, 2020)
In this article the concept of religion will be analyzed as it appears in the book Historia Eclesiastica Indiana by the Franciscan friar Gerónimo de Mendieta, concluded in 1596 and never published. The study will be inserted in the general debate about the re-invention of the concept of religion inside a colonial framework.